Strategy of School Principal Increases Quality of Education in Facing Asean Economic Communities (MEA) at SMK N 1 Bukittinggi - Ali Mutasar (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In this article, the researcher try see the phenomena about ASEAN Economic Community. Indonseia is kind of ASEAN Economic Communty must prepare quality of human resources to face ASEAN Economic Communty. The education is way to progress quality of human resources. SMK N 1 Bukiittingi is a education institution that express alumnus to word indurtry. In this research we going to role of head master of SMK 1 Bukittinggi to make quality of eduction to face ASEAN Economic Communty. I this research, researcher use qualitative method with phenomenology model. To get data, the researcher use interview and document study. Finding of research, to progressÂ  quality of education, the head master progress competence of teacher, student, development of curriculum and infrasrcture